Decomposition of Zircon in Mistastin Lake Impact Melt Glass: An Integrated SIMS, Hyperspectral-CL, Raman, and EPMA Study - Zanetti, M.; Wittmann, A.; Nemchin, Alexander; Carpenter, P.; Vicenzi, E.; Jolliff, B. (WILEY-BLACKWELL, 2014)
Multiple analytical techniques are used to examine two exceptionally well-preserved zircon grains entrained in glassy impact melt in order to study impact induced decomposition of zircon and determine the impact age from the dissolution reaction rim.